Analysis of the efficacy and safety of camrelizumab combined with chemotherapy for cervical cancer treatment - Yang, Song-Tian; Yang, Shuang; Wang, Ji; Mu, Xiao-Ling; Yan, Bo (Frontiers in Oncology, 2025)
IntroductionIn this study, we explored the effectiveness and safety of the immune checkpoint inhibitor camrelizumab in combination with chemotherapy for the treatment of cervical cancer by investigating adverse effects and changes in tumor volume, tumor activity, and biochemical indices.MethodsIn this retrospective analysis, the experimental group was administered intravenous camrelizumab in conjunction with a TP regimen (consisting of a paclitaxel analog and a platinum analog), while the control group was given only the TP regimen. The effectiveness of solid tumors, SCC-Ag values, tumor volume, and apparent diffusion coefficient (ADC) values, as well as adverse responses, were compared between the two groups.ResultsIn the experimental group, 11 cases (22.45%) exhibited complete remission (CR), 27 cases (55.10%) demonstrated partial resolution (PR), and 11 cases (22.45%) showed stable disease (SD). The objective remission rate (ORR) was 77.55%, and the disease control rate (DCR) was 100%. In the control group, 10 cases (25.64%) exhibited CR, 18 cases (46.15%) demonstrated PR, 9 cases (23.08%) exhibited SD, and 2 cases (5.13%) exhibited disease progression. The ORR was 71.79%, and the DCR was 94.87%. A significant difference was observed between the two groups regarding the post-treatment SCC-Ag value, pre-treatment minimum ADC (minADC), and the change in size of minADC before and after treatment (P < 0.05). A comparison of the pre- and post-treatment size changes in tumor volume in patients with stage IIA2 cancer revealed significant differences (p < 0.05). No adverse responses of grade 3 or higher were detected.DiscussionOur analysis showed that the combination of camrelizumab and chemotherapy effectively reduced tumor size and malignancy in cervical cancer treatment, demonstrating robust anti-tumor activity with a favorable safety profile.